IMPLEMENTASI TEORI BELAJAR SOSIAL DALAM PEMBELAJARAN PAI PADA MASA PANDEMI COVID 19 - Heni Eka Wati (TANJAK, 2022)
The application of Albert Bandura's social learning theory in learning Islamic education has the aim to find out the concept of Albert Bandura's social learning theory at SD Negeri Jetis 2 Yogyakarta, the reality of the application of Albert Bnadura's social learning theory in learning Islamic religious education and the supporting and inhibiting factors of the application of Albert's social learning theory Bandura in learning Islamic religious education at SD Negeri Jetis 2 Yogyakarta. This type of research uses qualitative research with a phenomenological approach. Sources obtained from the principal, Islamic Education teachers, parents, and students. In collecting data by means of observation, interviews and data analysis. The results of the study showed that the implementation of social learning theory from Albert Bandura in Islamic Education learning at SD Negeri Jetis 2 Yogyakarta went well with the concepts and principles of modeling (exemplary) with the use of media in the form of pictures and videos.